SIMPLIFIED IN VITRO PROPAGATION PROTOCOL FOR TACCA LEONTOPETALOIDES (L.) KUNTZE AND ASSESSMENT OF GENETIC UNIFORMITY OF REGENERATED PLANTLETS - Cepkova, Petra Hlasna; Vitamvas, Jan; Viehmannova, Iva; Kisilova, Jana; Cusimamani, Eloy Fernandez; Milella, Luigi (Emirates Journal of Food and Agriculture, 2015)
Tacca leontopetaloides is a tuberous species with nutritional, medicinal, and industrial potential. The aim of the present study was to develop a simplified micropropagation protocol for this species, combining phases of in vitro propagation and rooting, and to assess the genetic stability of in vitro regenerants using ISSR and flow cytometric analysis. In the first step, the effect of four cytokinins (BA, zeatin, kinetin, thidiazuron) at concentrations of 0.1-0.7 mg l-1 on shoot organogenesis was tested. The highest number of shoots was achieved on MS medium supplemented with 0.1 mg l-1 zeatin (4.11 ± 0.35 shoots/explant). Thereafter, this treatment was combined with auxins (NAA, IAA) at concentrations of 0.01-0.07 mg l-1 to study shoot organogenesis and in vitro rooting. A combination of plant growth regulators provided unchanged shoot organogenesis, while the root number per explant increased. The highest number of roots of all tested treatments was produced on MS medium supplemented with zeatin (0.1 mg l-1) in combination with NAA (0.05 mg l-1) (5.00 ± 0.38 roots/explant), suggesting that this medium may be used for both propagation and rooting. Well-rooted plants were transferred ex vitro, with a 97.78% survival rate. Ten randomly chosen in vitro regenerants were subjected to ISSR and flow cytometric analysis. Eleven ISSR primers produced 40 clear and reproducible bands per sample. All amplified products were monomorphic; no polymorphism was detected. Similarly, the results of flow cytometric analysis showed no variation in ploidy level. Thus, the micropropagation method optimized here can be used for highly effective production of true-to-type plants of T. leontopetaloides.